The innervation of chronic inflammatory human periapical lesions - Martinelli, C.; Rulli, M. A. (Elsevier, 1967)
Human periapical dental lesions (granulomata and cysts) were investigated for the distribution of nerve fibres. The lesions were fixed in 20% neutral-formaldehyde or 25% chloral-hydrate in 50% alcohol and stained by the Gross method (twenty specimens) and by the Nonidez technique (ten specimens). The microscopical examination showed that all lesions were richly innervated with myelinated, amyelinated and neurovegetative system fibres. The epithelial tissue of the cysticlesions was also innervated with fibres ending as 'boutons terminaux'. The evidence suggests that the neurovegetative system play an integral part in the mechanism concerned in the production of these chronic inflammatory lesions. © 1967.